Espectrometria de massas com ionização por paper spray e métodos quimiométricos aplicados à identificação de adulterações em açúcar e óleo de coco - Keila Heringer Mendonca (2018)
The increase in consumption and overvaluation of functional products functional became them subject to adulterations. The development of fast and reliable analytical methods applied to detection of such adulterations is necessary. Mass spectrometry by Paper Spray Ionization (PS-MS) stands out for its simplicity, speed and ability to analyze andquantify compounds in complex matrices. Chemometrics is a powerful analytical tool that assists in the interpretation of the large amount of data generated. In this work, a qualitative method to detect the addition of brown sugar in samples of coconut sugar and a quantitative method to determine the addition of hydrogenated vegetable fat in extravirgin coconut oil were developed. In the qualitative method, the PS-MS technique combined with the Partial Least Squares Discriminant Analysis (PLS-DA) was able to detect, unequivocally, additions of brown sugar between 2 and 30% m / m in 7 different brands of coconut sugar, which indicates a high robustness of the method, through a quick analysis and with minimum processing of the sample. The quantitative method,developed with the application of PS-MS technique and Regression by Partial Least Squares (PLS) technique, presented the same characteristics of speed and simplicity of analysis, being linear in the proposed work range. However, the method did not presentsatisfactory accuracy and some adjustments were necessary for its complete validation. The results obtained in this work reinforce the importance of PS-MS combined with chemometrics as an analytical technique for the detection of food fraud and adulteration,with the potential to be incorporated into the routine analysis of inspection agencies and food quality control laboratories.